Proceedings of the 22nd International ACM SIGACCESS Conference on Computers and Accessibility 2020
DOI: 10.1145/3373625.3417017
|View full text |Cite
|
Sign up to set email alerts
|

Value beyond function: analyzing the perception of wheelchair innovations in Kenya

Abstract: Innovations in the feld of assistive technology are usually evaluated based on practical considerations related to their ability to perform certain functions. However, social and emotional aspects play a huge role in how people with disabilities interact with assistive products and services. Over a fve months period, we tested an innovative wheelchair service provision model that leverages 3D printing and Computer Aided Design to provide bespoke wheelchairs in Kenya. The study involved eight expert wheelchair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The stories shared by people with disabilities in Study 2 showed a more nuanced perspective on AT that incorporated both positive and negative aspects. The perception of ATs as a tool that enhanced capabilities was definitely present, and it was also accompanied by an enhanced sense of embodiment akin to the one reported by participants in [ 46 , 70 ]. However, the role of ATs as identifiers of disability was seen as a lot more problematic as participants found that visible devices prevented them from blending in the crowd if they wished to do so [ 38 ], attracting unwanted attention and stigma [ 45 ], and even overshadowing their own identities [ 46 ].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The stories shared by people with disabilities in Study 2 showed a more nuanced perspective on AT that incorporated both positive and negative aspects. The perception of ATs as a tool that enhanced capabilities was definitely present, and it was also accompanied by an enhanced sense of embodiment akin to the one reported by participants in [ 46 , 70 ]. However, the role of ATs as identifiers of disability was seen as a lot more problematic as participants found that visible devices prevented them from blending in the crowd if they wished to do so [ 38 ], attracting unwanted attention and stigma [ 45 ], and even overshadowing their own identities [ 46 ].…”
Section: Discussionmentioning
confidence: 60%
“…A recent scoping review on barriers to AT access identified both disability stigma and discrimination as significant obstacles that could obstruct the uptake of AT, even when these are available and affordable [ 45 ]. Finally, research carried out with wheelchair users and providers in Kenya has shown that, although the functionality of ATs is important, considerations around identity, self-expression and presentation might play an even bigger role in AT choices [ 46 ]. In this paper, we explore the experiences and perceptions that Kenyans with and without disabilities have of AT, including perceptions of how AT impacts on disability stigma and discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, from an engineering point of view, studies on intelligent power wheelchairs (iChairs) and innovative wheelchair service provision models using 3D printing technology have also been reported [ 32 , 33 ]. In addition, customized seat research using 3D printing technology is also possible.…”
Section: Discussionmentioning
confidence: 99%
“…We will not go into much detail here, but additive manufacturing approaches are already in use or being developed for various AT-wheelchairs [67], hearing aid components [68], extensively in eyeglasses [69][70][71] with particular use in addressing provision for users with craniofacial abnormalities [72,73], prosthetics [74,75] and orthotics [76,77] as well as many others AT types. Much of this development is current at the research and development stage but work on the service approach in real LMIC settings is lagging.…”
Section: Potential Of Digital Fabricationmentioning
confidence: 99%